From 99-year Leases to Title Deeds: The Land Ownership and Productivity Enhancement Debate in Zimbabwe - Chimbari , Freddy; Kanyepe, James (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2025)
The article discusses the transition from the 99-year leases to the titling of land in Zimbabwe and the legalities that surround the policy framework transformation. Land ownership has been an area of contention in various countries, particularly for farmers who hold leases. Farmers continue to fail to access financial institutions due to the lack of collateral form of land ownership. Furthermore, financial institutions fail to recognise the offer letters and leases as bankable documents, creating investment problems for the farmers. The problem in the study is that the revised land titling in Zimbabwe provides an opportunity for land investment, but it also exposes poor farmers to debt traps by the elite that can lead to the foreclosure of various farms. The research uses a qualitative methodology with a bias towards case study research design. The research uses secondary information as the data collection method through the use of newspaper articles, since the issue of title deeds on land is new in Zimbabwe. Thematic data analysis is used as the data analysis method. The study reveals that the titling policy enhances productivity as farmers can use their land as collateral security to unlock land investment. The research concludes that the titling policy misses the mark of being a transparent policy as it fails to account for the use of corrupt government offices implicated in multiple corruption cases. The study recommends monitoring and evaluation of the titling process to reduce corruption from the deeds office